A Review on Pathophysiological Mechanisms, Clinical Heterogeneity, and Management of Takayasu Arteritis: Review Article (Journal of Pharma Insights and Research, 2025)
Takayasu arteritis (TA) is a rare, idiopathic, chronic granulomatous vasculitis that predominantly affects the aorta and its primary branches. Often referred to as "pulseless disease," it manifests primarily in women of reproductive age, particularly within Asian populations, although its global footprint is increasingly recognized. The disease course is characteristically biphasic, initiating with a systemic inflammatory phase marked by non-specific constitutional symptoms, followed by a chronic sclerotic phase resulting in vascular stenosis, occlusion, or aneurysm formation. This review discusses about the immunopathogenesis of TA, highlighting the interplay between genetic susceptibility specifically the Human Leukocyte Antigen (HLA) alleles and cell-mediated autoimmunity involving T-cells and macrophages. The clinical spectrum, ranging from silent progression to catastrophic vascular events such as aortic dissection and cerebrovascular ischemia is also discussed in this review. Diagnostic challenges persist due to the frequent dissociation between clinical symptoms and serological markers of inflammation, necessitating a reliance on advanced imaging modalities like Magnetic Resonance Angiography (MRA) and 18F-FDG PET/CT. Moreover, the therapeutic regimen is evolving beyond corticosteroids to include steroid-sparing immunosuppressants and novel biologic agents targeting specific cytokines like IL-6 and TNF-α. This review provides current literature to provide a cohesive understanding of TA, indicating the critical need for early detection and multidisciplinary intervention to mitigate morbidity and mortality